Pengaruh Pemberian Produk Olahan Kacang Kedelai terhadap Glukosa Darah Puasa dan Resistansi Insulin pada Model Tikus Diabetes Melitus - Kendra Hosea; Supriyanto Kartodarsono; Arifin; Sumardi (MEDICINUS, 2022)
Background: Diabetes mellitus (DM) is a chronic condition that requires continuous medical care with multifactorial management strategy. Soybean is known as source of isoflavones that possess beneficial effect to help controlling blood glucose level. This study aims to evaluate the effect of soybean product diet to reduce fasting blood glucose and improve insulin resistance. Methods: This is an experimental study using 30 streptozotocin-induced diabetic Wistar rats that divided into 5 groups, i.e. normal rats, negative control, and three treatment groups that receive tempeh, tofu, and soy flour diet for 2 weeks. Fasting blood glucose was tested before treatment, after diabetes induction, and at the end of the study. HOMA-IR was calculated using fasting blood glucose and fasting insulin level after diabetes induction and at the end of the study. MANOVA test was used to analyzed the data statistically (p<0,05). Results: There was a significant effect from soybean product diet (tempeh, tofu, and soy four) in reducing fasting blood glucose and HOMA-IR, with slightly better result shown in tempeh group. Conclusion: Soybean product such as tempeh, tofu, and soy flour have beneficial effect in reducing fasting blood glucose and improving insulin resistance in streptozotocin-induced diabetic rats.